Djerba, an island near Tunis (Architectural Review, 1965)
Keywords: Architecture -- Djerba

Djerba, paysage construit - Diaz, Paul (Carthage : revue culturelle tunisienne, 1965)
Keywords: Architecture -- Djerba

Djerba: a built landscape - Diaz, Paul (1965)
Keywords: Architecture -- Djerba

Tunisian Structure - Mitchell, Tim (Peace Corps volunteer, 1969)
Tunisian structures were of special interest to Volunteer Tim Mitchell when he was an architect-planner for Tunisia's public works ministry. Mitchell, who served in Tunisia from 1966 until last July, was enthusiastic about the possibility of “using traditional forms as a point of reference in developing modern Tunisian; responses to architectural and planning demands.” .. Mitchell took these photographs during his travels around the north African republic, and he acknowledges that not all the significant places and structures; of Tunisia are represented.
Keywords: Architecture -- Djerba

Villages in the sun : Mediterranean community architecture - Goldfinger, Myron (Praeger Publishers, Inc., 1969)
Keywords: Architecture -- Djerba

Sheep market, Djerba - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Djerba animal market - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Sunset, Djerba - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Djerba - Mud walls plastered - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Hammam (“Turkish Baths”, Honmt Souk. Djerba. I.IV.3.c.fig 1.) - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Veg market, Djerba - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Houmt Soukh - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Houmt Souk - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Houmt Soukh. Tunisia - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Houmt Souk - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Pot pile. Houmt Souk - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Houmt Souk - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Goats tethered, Houmt Souk - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Pottery, Djerba - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

White walls, Djerba - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Night Djerba - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Mosque. Djerba - Oliver, Paul (1967)
Keywords: Architecture -- Djerba

Djerba : étude de mise en valeur touristique - Beaudouin, Eugène; Baud-Bovy, Manuel (Société centrale pour l'équipement du territoire, 1960)
Keywords: Architecture -- Djerba; Ghuraba, mosquée al- (Houmt Souk, Djerba); Monuments -- Djerba; Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Tourisme -- Djerba

Geometry on Djerba - Harrison, Stephen (Architectural Review, 1965)
Keywords: Architecture -- Djerba